DEVELOPMENT OF FEMALE EDUCATION: HISTORY, PROBLEMS AND PROSPECTS (International journal of artificial intelligence, 2026)
Education serves as the cornerstone of human development and a primary catalyst for economic growth and social stability. However, the trajectory of women's education has been characterized by a long history of systemic exclusion, followed by gradual emancipation, and currently, a complex landscape of persistent inequality alongside significant progress. This scientific article provides a comprehensive analysis of the development of female education across three dimensions: historical evolution, contemporary structural and socio-cultural barriers, and future strategic prospects. By examining data from international organizations such as UNESCO and the World Bank, alongside historical case studies, this paper argues that while access to primary education has improved globally, deep disparities remain in secondary and tertiary levels, particularly in STEM fields and developing regions. The study concludes that achieving true gender parity requires not only policy reform but also a fundamental shift in cultural norms, increased investment in digital infrastructure, and targeted interventions to support women throughout their lifelong learning journeys.